An Empirical Study Of Learning Objects As Alternative Pedagogical Tool In Engineering Education - Sek, Yong Wee; Lau, Siong Hoe; Hasan Basari, Abd Samad; Hisham, Syariffanor; Law, Check Yee; Che Pee @ Che Hanapi, Ahmad Naim (2012)
This study aims to analyze the effectiveness of learning objects as alternative pedagogical tool in laboratory engineering education. 160 undergraduate students who enrolled in a Digital Systems course were randomly assigned to either a control group or an experimental group. This study utilized pre-test, post-test and postponed-test as the basis of data collection to measure the effectiveness of learning objects. The results show that the experimental group performance betters especially the low-achiever and medium-achiever sub-groups benefited more in increase and retention of knowledge and concept compare to the same sub-groups in the control group.